Öğretim Üyelerinin Araştırma Üretkenliği Kavramına İlişkin Algıları. - MAVĠġ SEVĠM, Üyesi Fazilet Özge; EMMĠOĞLU SARIKAYA, Esma (Afyon Kocatepe University Journal of Social Sciences / Afyon Kocatepe Üniversitesi Sosyal Bilimler Dergisi, 2023)
The aim of the research is to reveal the perceptions of academic member of the universities about the concept of research productivity. In the study structured with the phenomenology design, which is one of the qualitative research methods, the semi-structured interview form developed by the researchers was used as the data collection tool. In the research, it was tried to ensure that the study group consists of academic members with different academic degrees from various fields. For this reason, a total of 20 academic member with the title of doctor, associate professor and professor were reached in the fields of Social Sciences and Natural and Applied Sciences. MaxQda program was used to analyze the data, and the data were analyzed by using descriptive analysis method. Academicians generally defined research productivity as conducting research in the field of expertise, revealing new information, sharing information through publications and contributing to the field through all these activities. While explaining research productivity, they frequently used the concepts of qualified publication, visibility/noticeability, improvement, exploration of the unknown, generating ideas, solid/sustainable work, and production of scientific knowledge. The participants thought that in order to have research productivity, it was necessary to take part in activities such as writing articles, book/book chapters, participating conferences, congresses, workshops, presenting papers, giving/receiving training, participating collaborative work and projects, and obtaining patents. However, they emphasized that these activities should be evaluated in terms of quality instead of being evaluated in terms of number and they stated that they evaluated the quality of their publications according to the criteria of being published in high-impact journals and citation frequency.